Bendix Model 1030 Knudsen Cell Inlet System - Bendix Corporation (1960)
Multiple views of the interior and exterior of the Bendix Model 1030 Knudsen Cell Inlet System. Inlet systems are typically used to introduce samples into a mass spectrometer's ion source for analysis. The Knudsen Cell Inlet System allowed for rapid quantitative determinations of molecular weights and heats of vaporization, as well as qualitative determinations of molecular species in gas phase.
Keywords: Scientific apparatus and instruments; Spectrometer industry; Mass spectrometry; Time-of-flight mass spectrometry; Bendix Corporation